Clostridium difficile outbreaks: prevention and treatment strategies - Martinez, Fernando J (Dove Medical Press, 2012)
The incidence and severity of Clostridium difficile infection (CDI) have increased dramatically over the past decade. Its treatment, however, has largely remained the same with the exception of oral vancomycin use as a first-line agent in severe disease. From 1999 to 2004, 20,642 deaths were attributed to CDI in the United States, almost 7 times the rate of all other intestinal infections combined. Worldwide, several major CDI outbreaks have occurred, and many of these were associated with the NAP1 strain. This ‘epidemic’ strain has contributed to the rising incidence and mortality of CDI. The purpose of this article is to review the current management, treatment, infection control, and prevention strategies that are needed to combat this increasingly morbid disease.